НЕДОЛІКИ ТА ПЕРЕВАГИ КРЕДИТНО-МОДУЛЬНОГО НАВЧАННЯ В СФЕРІ ФІЗИЧНОГО ВИХОВАННЯ (Педагогіка вищої та середньої школи, 2008)
The article the analysis of scientific literature dealing with the problems of the development of physical training according to the Bologna Process.